Development of environmental and natural vulnerability maps for Brazilian coastal at Sao Sebastiao in São Paulo State - Furlan, A. [UNESP]; Bonotto, Daniel Marcos [UNESP]; Gumiere, S. J. [UNESP] (Springer, 2011)
In this study, environmental and natural vulnerability maps developed for a Brazilian coastal region at Sao Sebastiao City in São Paulo State helped to address a better understanding of the ecosystem fragility. Intense anthropogenic activities take place in the site that are mainly related to the petroleum industry and involve the operation of refineries and storage/transport of gas/oil by pipelines. A Geographical Information System (GIS) allowed the maps elaboration and analysis, where the region vulnerability was classified into five indexes: very low, low, medium, high and very high. The results depicted well the most vulnerable areas in the site, which should receive special care for their preservation. They include the coastal zones, the fluvial marine plain, the mangrove and the urban area of Sao Sebastiao City. The results reported herein also show that the approach utilized may provide the decision makers with tools to develop an integrated coastal zone management for preserving the environmental resources in Sao Sebastiao municipality. The methodology adopted is of easy implementation and adaptation to other areas, only taking into account the decision rules fitting diverse criteria imposed by the new reality.
Keywords: GIS; Environmental and natural vulnerability; Coastal zone; Ecodynamic